L'Égyptienne - Karttunen, Assi; Rameau, Jean-Philippe 1683-1764; d'Anglebert, Jean-Henri 1629-1691 (Finland Alba Records Oy, 2008)
Jean-Philippe RAMEAU (1683-1764)L'Entretien des MusesSuite in a minor (c.1728)Suite in G/g minor (c.1728)Jean-Henry D'ANGLEBERT (1635-1691)Chaconne de PhaetonAssi Karttunen (harpsichord)rec. 2008-2009, Östersundom Church, Sipoo, Finland. DDDALBA ABCD 290 [69:53]Jean-Philippe Rameau's Nouvelles Suites de Pièces de Clavecin dates from around 1728 and it consists of two suites. The first, in A minor, is more traditional and ends with a massive Gavotte and no fewer than six variations. The second, in G major and minor, is a set of different character movements somewhat remote from the conventional dance suite.The Parisians had an insatiable curiosity about distant lands and peoples. Among the works of Rameau there are some that allude to the peculiar inhabitants of the countries visited by explorers: Africans, Indians and Persians.Within their small-scale context the Nouvelles Suites highlight the things with which Rameau set music moving along a new track. The collection begins with the dance-suite tradition and ends with pieces that in their own way brought about a harmonic revolution, leading to instrumental art divorced from words. Rameau was criticized for many of these things. The suites were for him a musical journey of discovery by a wandering and ever curious vagabond (l'Égyptienne), the composer himself.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Keyboard music; Harpsichord; Orientalism; France